2019
DOI: 10.4097/kja.19186
|View full text |Cite
|
Sign up to set email alerts
|

Whole body ultrasound in the operating room and intensive care unit

Abstract: Whole body ultrasound can be used to improve the speed and accuracy of evaluation of an increasing number of organ systems in the critically ill. Cardiac and abdominal ultrasound can be used to identify the mechanisms and etiology of hemodynamic instability. In hypoxemia or hypercarbia, lung ultrasound can rapidly identify the etiology of the condition with an accuracy that is equivalent to that of computed tomography. For encephalopathy, ocular ultrasound and transcranial Doppler can identify elevated intracr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 118 publications
(130 reference statements)
2
12
0
Order By: Relevance
“…34 Bedside ultrasound could be useful in detecting associated pulmonary complications or non-pulmonary complications such as cardiac dysfunction that can occur in such patients. 46 Combining heart, lung, deep veins examination 41 and whole-body ultrasound 47,48 can identify the mechanism, 49 risk factors, 50 and life-threatening conditions in patients with respiratory symptoms (Fig. 5).…”
Section: Role Of Lung Ultrasound Monitoringmentioning
confidence: 99%
“…34 Bedside ultrasound could be useful in detecting associated pulmonary complications or non-pulmonary complications such as cardiac dysfunction that can occur in such patients. 46 Combining heart, lung, deep veins examination 41 and whole-body ultrasound 47,48 can identify the mechanism, 49 risk factors, 50 and life-threatening conditions in patients with respiratory symptoms (Fig. 5).…”
Section: Role Of Lung Ultrasound Monitoringmentioning
confidence: 99%
“…Furthermore, an advantage of ultrasound is its real-time accessibility. In this case, bedside detection using ultrasonography was performed immediately after the event [ 13 ]. However, it would have been more appropriate to use needle thoracotomy immediately after ultrasound as the first diagnostic tool of choice before CXR or arterial blood gas analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The latter three signs were identified, but the first sign, the lung point, was not observed in our case. In the diagnosis of pneumothorax, the lung point is considered a pathognomonic sign, and only in cases with absence of lung sliding without the lung point, other diagnostic modalities are required [ 9 , 13 ]. In patients who are unstable or in cardiac arrest, the conventional methodology with a step-by-step procedure for the detection of the four ultrasound signs varies slightly.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the Apprentissage de l'Echographie Pulmonaire Study Group found that 25 supervised examinations are required for competence in lung US, 5 and lung US has excellent accuracy for differentiating basic causes of respiratory failure 6 . Additionally, whole‐body US protocols have been published for the evaluation of hemodynamic instability, hypoxemia, encephalopathy, and oligoanuria among other conditions 7 . Although the diagnostic accuracy of each of these protocols is beyond the scope of this brief, narrative review, POCUS is providing decision support to clinicians 8,9 …”
Section: Chronologic Surveymentioning
confidence: 99%
“…6 Additionally, whole-body US protocols have been published for the evaluation of hemodynamic instability, hypoxemia, encephalopathy, and oligoanuria among other conditions. 7 Although the diagnostic accuracy of each of these protocols is beyond the scope of this brief, narrative review, POCUS is providing decision support to clinicians. 8,9 Consequently, used as a comprehensive, multiorgan assessment tool offering repetitive US assessments during the extended course of a patient's ICU stay, POCUS is undergoing a paradigm shift, moving its focus from a qualitative toward a quantitative assessment of pathologic processes.…”
mentioning
confidence: 99%